Effect of an Ayurveda treatment for chronic palmoplantar eczema: An experience - Manisha Kapadiya; Tukaram Sambhaji Dudhamal (Wolters Kluwer Medknow Publications, 2023)
Palmoplantar eczema is an ill-defined and poorly understood condition, yet rebellious to therapy. A 29-year-old nondiabetic female patient with hyperkeratotic palmoplantar eczema eczema complained of swelling and pus discharge from both feet for the past 3 days. She had a history of fever 3 days back, thick scaling from the palms and soles in the past 9 months, itching, and hyperpigmented lesion in both the palm and sole since 1 year associated with vidagdhajirna (~indigestion). Pus culture revealed Klebsiella pneumoniae isolated from pus-discharging fissures. The Ayurvedic diagnosis was made as "Padadari" (~cracked plantar sole/palm), and the patient was managed accordingly. There was no datum published yet that palmoplantar eczema is managed by the Ayurvedic line of management; thus, this treatment protocol is based on the status of the Prakriti (~body constitution) of the patient, Ajirna, Kala (~time/season), and Rasayan Chikitsa (~rejuvenation and revitalization therapy). Scaling, itching, and hyperpigmented lesion markedly decreased in both the palm and sole. Inflammation in the feet and pus discharge completely ceased after 15 days of consistent treatment, and a complete regression of disease occurs after 2 months. There were no relapses of lesions up to 2 years of follow-up. This single case report demonstrates that hyperkeratotic palmar plantar eczema can be successfully managed through rejuvenating Ayurveda treatment.